Responding to COVID-19 with IT: A Transformative Moment? - de Wit, Hans; Altbach, Philip (International Higher Education, 2020)
Due to the COVID-19 crisis, higher education is being forcibly transformed. But questions must be asked: Is the distance revolution working, and are we in a “transformative moment”? Today, distance education is ubiquitous—of necessity. However, it is not necessarily very successful. Most probably, hybrid or blended education, will expand. Just as MOOCs, a decade or so ago, did not produce the educational revolution that many predicted, today’s massive and hurried shift to distance education will not either.